EVALUATE THE EFFECTS OF MICRONEEDLING IN THE TREATMENT OF STRETCH MARKS - Samira Fontenele de Araujo, Antonia; Cardoso Nunes, Tarciana (Health and Society, 2023)
Introduction: Stretch marks are classified as linear lesions that appear on the skin due to the external mechanism that triggers tissue stretching and internal mechanism, which occurs due to genetic markers, accelerated growth and muscle mass gain. In the internal mechanism, it occurs due to genetic markers, accelerated growth and muscle mass gain, with an incidence in specific regions such as buttocks, abdomen and breasts. Microneedling is an innovative technique, which aims at the production of collagen through the mechanical stimulus generated by the rolling of the dermaroller, equipment used for the treatment of integument disorders such as stretch marks. Objective: This study aims to carry out a literature review of the regulated microneedling procedure for the use of physical therapists in the treatment of stretch marks. Materials and methods: The present study used an integrative literature review through the analysis of articles published in national and international scientific journals. A critical search of the scientific literature focused on studies that demonstrated positive results in the use of microneedling in patients with stretch marks, using the following indexed databases: Lilacs, Medline, DECs (Descriptors in Health Sciences) and Coleciona SUS (Brazil) . Results: After an initial survey, reading titles and abstracts, 11 articles were found, later, after reading all the articles critically, paying attention to the inclusion and exclusion criteria, 05 articles were selected to compose the results and discussion of this article. Conclusion: Through this study, it can be concluded that microneedling is a great option for the treatment of stretch marks, significantly improving their appearance. In addition to its remarkable effects, it must be taken into account that it is a low-cost procedure when compared to others. It was noticed that there are few studies and research that deal with the topic addressed. However, it is suggested that further studies can be carried out with a larger sample and with the isolated use of microneedling in the treatment of stretch marks.